Corporate anti-corruption disclosure: An examination of the impact of media exposure and country-level press freedom. Issue 8 (16th October 2017) - Blanc, Renata; Islam, Muhammad Azizul; Patten, Dennis M.; Branco, Manuel Castelo
Abstract : Purpose: The purpose of this paper is to investigate whether differences in media exposure regarding corporate corruption appear to influence companies' anti-corruption disclosures. The authors also examine whether the level of press freedom in firms' home countries affects disclosure and the impact of media exposure in different ways. Design/methodology/approach: The authors use Transparency International's 2012 ratings of anti-corruption disclosure by the 105 largest multinational firms in the world, press freedom assessments from the non-governmental organization Reporters Without Borders, and media exposure measures based on a search using the Dow Jones Factiva database. The authors assess relations using regression analysis controlling for other firm-specific factors potentially impacting disclosure choices. Finally, the authors consider the potential effect of other country-level factors. Findings: The results indicate that media exposure, using either an existence or an extensiveness measure, is positively related to differences in sample companies' anti-corruption disclosures. The authors also find that disclosure is more (less) extensive where home country press freedom is less (more) restricted and that reduced press freedom appears to reduce the impact of media exposure on the disclosure. The authors further document that press freedom levels explain more difference in anti-corruption disclosures than other country-level factors potentially influencing the practice. Research limitations/implications: Because the investigation is limited to very large international firms for a single year, the degree to which the findings apply to other companies and time periods cannot be assessed. Further, the authors cannot determine how the findings would hold using an alternative disclosure rating scheme. Finally, the authors do not assess whether differences in the source of media exposure impact the findings. Social implications: The findings suggest that, to the extent that improved anti-corruption disclosure reflects greater corporate attention to corruption issues, the media may be a powerful player in addressing this social ill. Unfortunately, the results also indicate that media efforts may not be sufficient to bring about change in locations where the freedom of the press is limited. Further, the results suggest that disclosure appears to be a function of exposure to social and political exposures, and the authors therefore question whether it will actually lead to improved corruption performance. Originality/value: The study is the first to consider the impacts of media exposure and press freedom on corporate social disclosures.